Demonstration of the Effectiveness of a Pilot, Variable Speed Crusher Featuring an In‐Line Oxygen Dosing System. Issue 6 (14th April 2022) - Angeloni, Giulia; Guerrini, Lorenzo; Corti, Ferdinando; Spadi, Agnese; Calamai, Luca; Parenti, Alessandro; Masella, Piernicola
Abstract: At the industrial scale, improvements to extra virgin olive oil (EVOO) processing are an important opportunity to increase both added‐value, and the product's organoleptic and chemical parameters. Concerning all the operations used during EVOO extraction, crushing and malaxation have an effect on the extraction efficiency and minor components composition extremely significant. In this context, a pilot industrial‐scale crusher is designed and developed that can control the amount of oxygen that is dosed directly into the produced olive paste. In this study, the effectiveness of this new technique, combined with different crushing speeds on EVOO quality, is evaluated. It is demonstrated that supplying oxygen to the paste enriches the volatile fraction, the mean increase is about 30% for the compounds associated to positive sensory notes, while the concentrations of the compounds associated to sensory defects are stationary on 5.2 mg kg −1 . Practical Applications : This result is confirmed by a sensory analysis, notably an increase in fruity intensity. It is also shown that crushing speed affects the extraction of compounds such as biophenols, and increases the bitter taste. Increased bitterness is detected for samples crushed at 3500 rpm compared to those crushed at lower speed (mean 5.7±0.3 compared to 4.5±0.4). Abstract : This study investigates the relationship between the oxygen concentration and crusher speed on extra virgin olive oil quality. The higher speed of rotation of the breaking organs significantly increases the content of some phenolic compounds of the class of secoiridoids. The minimum oxygen supply increases the positive volatile compounds and the concentration of negative aromatic compounds (off‐flavors) is not changed.